LOGISTIK MARITIM DAN KONEKTIVITAS KAWASAN KEPULAUAN Studi Kasus Kabupaten Muna - Harpiang Wardiningsih; Eliyanti Agus Mokodompit (STIE ENAM ENAM KENDARI, 2025)
Maritime logistics plays an important role in supporting the connectivity of island regions such as Muna Regency located in Southeast Sulawesi. This research aims to analyze the condition of maritime logistics and the challenges of regional connectivity in the archipelago with a case study approach. The research used a descriptive qualitative method with data collection techniques through interviews, observations, and document studies. The results showed that limited port infrastructure, inconsistent shipping schedules, and high logistics costs are the main obstacles to regional connectivity. However, there is strategic potential from Muna's geographical position in the regional sea trade route. An integrated port development strategy and increased intermodal integration are needed to strengthen regional connectivity